DEVELOPING AND VALIDATING AN ORGANIZATIONAL COMPETENCY SCALE (OCS) FOR ELDER CIVIC ENGAGEMENT PROGRAMS. (11th November 2018) - Chen, H; Ma, F
Abstract: This pilot study aims to develop and validate an Organizational Competency Scale (OCS) for elder civic engagement programs. The OCS was used to comprehensively measure the organizational competencies at the micro, mezzo, and macro levels. In total, 32 formal organizations in the State of Texas participated in the pilot study, most of which were local non-profit organizations and implemented their programs on a regular basis. There were four types of organizations, including recreational organizations, social service organizations, government agencies, and an educational organization. Based on the factor analyses of data collected from these organizations, the original 31-item OCS was reduced to a 28-item, seven-factor scale. The derived seven factors were client discovery with support, client-centered planning and management, client assessment and training, integration of diverse groups, promotion of adaptation between groups, integration of resources to address the structural constraints, and promotion of social recognition and social justice. Further, the findings from the reliability tests and hierarchical regression analysis supported the reliability and criterion-related validity of the OCS. As a reliable and valid tool, the OCS can be used by formal organizations to evaluate the current competencies, identify areas for improvement, and find future directions for organizational development. The OCS can also serve as practice guidelines to help organizational practitioners integrate available resources within the multi-level systems to better engage and serve older participants.